Agronomic performance, flowering, physicochemical characteristics and genetic divergence in garlic accessions from Brazil. - TAULA, A. J. V. (2021)
The objective of this work was to assess the agronomic performance, flowering capacity and genetic divergence of 13 experimental garlic accessions bred in Brazil. The experiment was laid out as a completely randomized block design with four replications at Lavras, Minas Gerais, Brazil from May to October 2018. A total of 11 accessions were experimental and two were control varieties, Quitéria and Caçador.